2022
DOI: 10.1177/11795476221139396
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Reference Syndrome Treated With Lurasidone and Cognitive Behavioral Therapy: A Case Report

Abstract: Olfactory Reference syndrome (ORS) is characterized by patients falsely believing that they exude a foul body odor, which is embarrassing and disturbing to the patient. The increased anxiety due to this belief leads to compulsive behaviors, social anxiety, and functional impairment. ORS poses enormous challenges in its diagnosis and treatment. The disorder can be often treatment-resistant or recurrent. A case formulation followed by a classificatory diagnosis is an effective approach to distinguish it from oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Another potential for ORD treatment is cognitive behavioral therapy (CBT). Some previous case reports have suggested that utilizing CBT adjusted for obsessive–compulsive disorder (OCD) models could potentially reduce ORD symptoms 4,9,10 . The CBT model has been successful in treating female patients in the UK, the USA, and Australia 4,10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another potential for ORD treatment is cognitive behavioral therapy (CBT). Some previous case reports have suggested that utilizing CBT adjusted for obsessive–compulsive disorder (OCD) models could potentially reduce ORD symptoms 4,9,10 . The CBT model has been successful in treating female patients in the UK, the USA, and Australia 4,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Some previous case reports have suggested that utilizing CBT adjusted for obsessive–compulsive disorder (OCD) models could potentially reduce ORD symptoms. 4 , 9 , 10 The CBT model has been successful in treating female patients in the UK, the USA, and Australia. 4 , 10 , 11 However, its applicability in East Asia, including Japan, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation